2002
DOI: 10.1016/s0891-5849(01)00827-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular cysteines define ectopeptidase (APN, CD13) expression and function

Abstract: Alanyl aminopeptidase (APN) is a surface-bound metallopeptidase that processes the N-terminals of biologically active peptides such as enkephalins, angiotensins, neurokinins, and cytokines. It exerts profound activity on vital processes such as immune response, cellular growth, and blood pressure control. Inhibition of either APN gene expression or its enzymatic activity severely affects leukocyte growth and function. We show here that oxidoreductase-mediated modulations of the cell surface thiol status affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…2d), suggesting that disulfide formation in endoglin depends on mitochondrial ROS. Such disulfide-dependent antibody recognition also was reported previously for the cell-surface protein CD13 (13).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2d), suggesting that disulfide formation in endoglin depends on mitochondrial ROS. Such disulfide-dependent antibody recognition also was reported previously for the cell-surface protein CD13 (13).…”
Section: Resultssupporting
confidence: 85%
“…2e), but not platelet/endothelial cell adhesion molecule (PECAM), was eliminated, whereas staining within the Golgi increased. The alteration of surface expression also has been reported for CD13 with a disulfide-forming cysteine site mutant (13). Similarly, previous studies showed that disulfidebound proteins are reduced and reversibly retained in the ER in DTT-treated cells, whereas proteins entering the secretory pathway are not (14).…”
Section: Resultssupporting
confidence: 69%
“…Aminopeptidase N (APN/CD13), a Zn 2+ -dependent ectopeptidase localized on cell surface, is a transmembrane protein that cleaves N-terminal neutral amino acids of various peptides and proteins [1,2]. In a classic report, a signiWcant correlation between APN/CD13 expression and metastasis of lung carcinoma was observed in patients with squamous cell carcinoma and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Aminopeptidase N (APN/CD13) is a type II membranebound metalloproteinase, which is expressed on several types of cells including intestinal epithelium, liver, placenta and lung [1,2]. APN/CD13 has a variety of functions, such as inXammatory and immunological responses, signal transduction, antigen processing and cytokine degradation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is a ubiquitous enzyme expressed in many kinds of tissues, organs, and cells [2,3]. APN can remove the amino acid from the unsubstituted terminus of biologically active peptides, such as enkephalins, angiotensins, neurokinins, cytokines [4].…”
Section: Introductionmentioning
confidence: 99%